The Association of Perceived Meta Ads Exposure and Content Quality With Brand Awareness: A Case Study of Kursusmengemudi.Id - A. Galung Astaqi; Nyoman Indah Kusuma Dewi; I Komang Mahayana Putra (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the association of perceived Meta Ads exposure and content quality with brand awareness among audiences of Kursusmengemudi.id, a client of PT Whello Indonesia Prima. A quantitative cross-sectional survey was conducted with 100 purposively selected respondents who had viewed the brand’s advertisements or followed its social media account. Data were collected through a five-point Likert-scale questionnaire and analyzed using instrument testing, descriptive statistics, classical assumption tests, multiple linear regression, t-tests, an F-test, and the coefficient of determination. Perceived Meta Ads exposure was positively and significantly associated with brand awareness (t = 3.433; p = 0.001), as was content quality (t = 4.395; p < 0.001). The regression model was statistically significant (F = 160.547; p < 0.001) and explained 76.8% of the variation in brand awareness. The standardized coefficient for content quality (β = 0.504) was larger than that for perceived Meta Ads exposure (β = 0.394), although the difference between the coefficients was not statistically tested. Within this sample, the findings indicate that digital advertising exposure and the relevance, attractiveness, clarity, and consistency of content are jointly associated with stronger brand recognition and recall